PENGARUH ASIMETRI INFORMASI TERHADAP BUDGETARY SLACK DENGAN KEJUJURAN SEBAGAI VARIABEL PEMODERASI: PENGANGGARAN PARTISIPATIF (Studi Eksperimen Pada Mahasiswa S1 Akuntansi Universitas Muhammadiyah Bengkulu) - Yudi Pratama Putra (UNIVED Press, 2020)
Yudi Partama Putra ; The population of this study is the S1 students of the 2015 Academic Year of Muhammadiyah University of Bengkulu. The number of participants who participated in the experiment is 123 students. The technique of taking samples was using purposive sampling with the criteria of samples had completed Management and Public Sector Accounting. Method of data collection used was through experimental method by using questionnaires and manipulation on research subjects. The validity test used was Pearson Product Correlation test, while the reliability test used was Cronbach Alpha. The hypothesis test used in this research was ANOVA which was accompanied by Post Hoc tukey test. The Research results showed that: 1) The level of information asymmetry has an influential information on the budgetary slack. It was shown by F-count > F-table, which is 8.302> 2.68 and p-value 0.000; 2) The Honesty influenced the correlation between information asymmetry and the budgetary slack. This is shown by F-count > F-table, which was 4,785 < 2.68 and p-value 0.010 <0.05; and 3) The results of tukey HSD and bonferoni showed that there was a difference between low and medium information asymmetry with a difference of 0.77401 and statistically significant with p = 0.0428. The difference between low information asymmetry and high information asymmetry was 0.339581 with a significance of 0.0000, the difference between moderate information asymmetry and high asymmetry was 0.339580 and the difference between medium and high asymmetry was 0.262179 with a significance of 0.003. Key Words: Budgetary slack, information Asymmetry, Honesty